Novas metodologias para as aulas de botânica no ensino médio: sequência didática, jogo e herbário virtual - Luiza Cecília Marian Barud Torres (2020)
Botany content in high school is sometimes neglected by some students and teachers due to the formatting of content and the impossibility of carrying out practices in the laboratory or in the field. Audiovisual resources are excellent teaching tools, but the opportunity to place the student in front of his or her object of study, vegetables, can give new meaning to academic and personal experiences. This study demonstrates the partial application of a didactic sequence in a 2nd year high school class at a state school in the city of Belo Horizonte, and its central object is a game of riddles and a virtual herbarium hosted on a blog. The diagnostic test revealed the ignorance of the presence of vegetables in the students' daily lives, which is treated by the literature as botanical blindness. Due to the incomplete application of the game, the data, which would initially be analyzed, was compromised, but it was possible to carry out a critical analysis of the methodology and restructure the educational products generated based on the evaluation of masters and students of PROFBIO. We hope other teachers would be able to use the didactic sequence, totally or partially, in their praxis, and that it would contribute to the teaching of botany in schools.